District administrator perspectives of current and ideal approaches to identifying and supporting student social, emotional, and behavioral needs - Chafouleas, Sandra M.; Cintron, Dakota W.; Koslouski, Jessica B.; Briesch, Amy M.; McCoach, D. Betsy; Dineen, Jennifer N. (Frontiers in Education, 2024)
Leadership support has been identified as a key facilitator to successful implementation of schoolbased initiatives. School leadership contributions to student academic success and school reform have been documented, but less work has focused on the effects of leadership on school mental health initiatives such as social, emotional, and behavioral (SEB) screening. Few studies have investigated administrator knowledge and support for SEB screening or compared their current and ideal approaches to SEB screening, both of which are important to informing directions for implementation supports. Using a nationally representative sample of U.S. public school districts, we investigated tensions between school district administrators' (n = 1,330) current and ideal approaches to social, emotional, and behavioral (SEB) screening within the current study. Nearly half of administrators (46.7%) reported using an approach to SEB screening that was not their ideal approach. We fit binomial and multinomial logistic regression models to determine predictors of positive, negative, or no tensions based on the administrators' current approach to SEB screening, administrators' beliefs about the role of schools in student SEB, and district demographics. Higher beliefs scores commonly predicted administrator desire for more proactive approaches, whereas district characteristics yielded varied results. Results call for targeted next steps, including implementation supports, funding, and knowledge building aligned with administrator and district characteristics.